A mediation analysis of meteorological factors on the association between ambient carbon monoxide and tuberculosis outpatients visits - He, Tianfeng; Qian, Xujun; Huang, Jing; Li, Guoxing; Guo, Xinbiao (Frontiers in Public Health, 2025)
BackgroundAmbient carbon monoxide (CO) exposure has been identified as an emerging environmental risk factor contributing to the progression of pulmonary tuberculosis (PTB). However, the epidemiological evidence remains inconsistent. This study aims to investigate the short-term association between low-level CO exposure and PTB outpatient visits in a developing region.MethodsWe conducted a time-series study utilizing a distributed lag non-linear model (DLNM) combined with mediating effect analysis, based on daily CO and PTB cases from 2011 to 2020 in Ningbo, China.ResultsAmong all patients with PTB, a 0.1 mg/m3 increase in CO concentration was associated with an increased risk of PTB outpatient visits in the single-pollutant model, particularly at lag days 2–6. The maximum relative risk (RR) was 1.091 (95%CI, 1.020–1.168, lag 0–2 days). Similarly, the maximum cumulative lag effect of CO exposure was 1.781 (RR = 1.781, 95%CI: 1.157–2.742, lag 0–15 days). Subgroup analysis revealed a significant effect of CO exposure in males (RR = 1.090, 95%CI: 1.009–1.777, lag 0–3 days), females (RR = 1.101, 95%CI: 1.014–1.195, lag 0–3 days), younger individuals (RR = 1.097, 95%CI: 1.022–1.178, lag 0–2 days), and during the warm season (RR = 1.012, 95%CI: 1.002–1.022, lag 0–4 days). Mediation analysis indicated that temperature had an indirect mediating effect on association between CO and PTB (−0.0065, 95%CI: −0.0130 to −0.0004), while air pressure, visibility, and humidity showed no significant mediating effects.ConclusionOur findings indicate that ambient CO exposure, even at low levels, has a short-term impact on PTB in developing regions. Temperature plays a partial mediating role in this relationship. Consequently, it is critical to enhance environmental monitoring and early warning systems to effectively address the prevalence of PTB and the delays in health-seeking behavior.